Hubungan di antara pendidikan dengan perkembangan kognitif dan sosio-emosi di kalangan kanak-kanak prasekolah - Azwandi, Mohamad (2008)
This research is aimed to identify the relationship between characteristic of preschool quality (activity, teaching aids, physical infrastructure, interaction, monitoring and timetable) with the cognitive development and socio-emotional among the child. The study also to explore the existing characteristics of preschool quality at the government preschool and at the private preschool based on parents perspective. The research also tries to identify whether existing significant differences positively between the development of child at the government preschool and private preschool. There are four preschool involved in this study, they are two from government preschool and too from private preschool. A11 the four preschools are located in the district of Kuala Terengganu. There are about 100 parents involved in the survey (50 from government preschool (n=50) and 50 from private preschool (n=50). The research analysis data used Pearson correlation statistic analysis, regression analysis and T-Test. The results show important relationship between preschool characteristic quality and the development of cognitive and socio-emotional of the child among the undependent variables that is activity, teaching aids, physical support, interaction, monitoring and timetable. That is dominant in contributing the development of the child's is monitoring and activity. In conclusion, this research has shown frame of theory that the quality of preschool characteristic education do give a great impact the development of the child